Effects of high ellagic acid concentration raspberry (Rubus idaeus) extract on apoptotic miRNA expressions in neuroblastoma cell lines (SH-SY5Y) - Demirci, A.; Yildirim, S.; Aktemur, G.; Durcanoglu, N.; Aslan, E.; Askin, S.; Durmuş, Mahmut (Pergamon-Elsevier Science Ltd, 2018)
[No abstract available]
9th International Eurasian Hematology Oncology Congress (EHOC) -- OCT 17-20, 2018 -- Istanbul, TURKEY